1990
DOI: 10.1203/00006450-199011000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Artery Ligation in the Maternal Rat Alters Fetal Tissue Glucose Utilization

Abstract: LcI [2DG]t dt o [glucose] MAT ERIALS AND METHODSby which these conditions retard fetal growth and the processes th at are responsible for the neonatal hypoglycemia are not completely understood.Maternal uterine art ery ligati on has frequentl y been used to study the consequences of redu ced uterine blood flow on the fetu s. Th is procedur e severely retard s fetal growth in the rat (4-10). Previou s studies using this model have suggested that lim ited fetal nutrient availability and altered placental gaseous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…By comparison of both groups with placentas from un‐operated control dams, we demonstrate an immediate, longitudinally stable reduction of GLUT‐1 in LIG placentas and a short reduction on day E20 in SOP placentas. Consistent with a down‐regulation of placental glucose transporters, it was demonstrated that fetal‐maternal glucose ratios are persistently reduced 24 and 48 h after uterine artery ligation [Lueder and Ogata, ]. Together with relatively increased fatty acid transport, this may result in a decreased respiratory quotient of the LIG and also SOP fetuses, with may have significant impact on programming energy metabolism.…”
Section: Discussionmentioning
confidence: 87%
“…By comparison of both groups with placentas from un‐operated control dams, we demonstrate an immediate, longitudinally stable reduction of GLUT‐1 in LIG placentas and a short reduction on day E20 in SOP placentas. Consistent with a down‐regulation of placental glucose transporters, it was demonstrated that fetal‐maternal glucose ratios are persistently reduced 24 and 48 h after uterine artery ligation [Lueder and Ogata, ]. Together with relatively increased fatty acid transport, this may result in a decreased respiratory quotient of the LIG and also SOP fetuses, with may have significant impact on programming energy metabolism.…”
Section: Discussionmentioning
confidence: 87%
“…While studying the long-term conse quences of ischemia on glucose transport and utilization in the fetal brain, Lueder and Ogata [14] showed that glucose utilization was reduced, 24 h after unilateral uterine artery ligation. At this time, cerebral glucose transport in the fetus did not differ from the control [15], In a different experimental model, cesarean-delivered preterm rats subjected to anoxia showed a substantial reduction in brain glucose levels in spite of adequate lev els of glucose in the circulation [8].…”
Section: Kinetics Of2d-glu Transportmentioning
confidence: 99%
“…In our group, we have taken the approach of looking at representative “candidate” genes in multiple disparate models of perinatal insult. We have used animal models ranging from IUGR, produced by UPI (Lueder and Ogata, 1990; Lane et al, 1996) and maternal malnutrition (Desai et al, 2008), to mechanical ventilation (Albertine et al, 1999) to test the hypothesis that significant changes in the perinatal environment can 1) increase the risk of associated adult morbidities, such as diabetes; 2) affect perinatal and postnatal gene expression of the same candidate genes; and 3) modify the chromatin structure of relevant candidate genes.…”
Section: Uncovering the Mechanistically Important Aspectsmentioning
confidence: 99%